An Event Study of the NSE sector wise indices : Case of Covid 19 (International Journal of Food and Nutritional Sciences, 2020)
The new type of coronavirus outbreak came to light on 31st December, 2019 when China informed the World Health Organisation of a cluster of cases of pneumonia of an unknown cause in Wuhan city in Hubei Province. The globe has gone under a huge change due to the pandemic. The consumer spending has gone down. Since June, 2019, wholesale deflation was at 3.21% this year which marked the headline inflation. Wholesale inflation was negative. And the country stood at the verge of entering recession.All of this news is reflected in the stock markets. A stock market can give a small glimpse of what is happening in the economy of a country. Stock exchanges across the whole world show ups and downs with every news in the market and is relevant to the economy.This paper is an event study of response of 12 Nifty sectoral indices in response to COVID-19.